2013
DOI: 10.5539/jas.v5n2p204
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Extension Services: A Case Study of Farmers in Amathole

Abstract: The trend in the contemporary society for accountability calls for the evaluation of extension services. Extension service providers should be saddled with the responsibility of ensuring that farmers are continually satisfied with services being delivered. In enhancing farmers’ loyalty and confidence, extension feedback is becoming increasingly paramount. Customer satisfaction survey remains an essential tool for measuring the quality of services and outcome of programmes. The purpose of the study was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Reliability analysis for internal consistency of the scale was undertaken by calculating its Cronbach's α value; classifications of Cronbach's α coefficient indicate strong reliability if the α coefficient exceeds 0.7 (Agholor et al, 2013). Cronbach's α for actual and proposed ratings for the surveyed indicators for this study ranged from 0.728 to 0.963, implying strong internal consistency and reliability.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Reliability analysis for internal consistency of the scale was undertaken by calculating its Cronbach's α value; classifications of Cronbach's α coefficient indicate strong reliability if the α coefficient exceeds 0.7 (Agholor et al, 2013). Cronbach's α for actual and proposed ratings for the surveyed indicators for this study ranged from 0.728 to 0.963, implying strong internal consistency and reliability.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…This finding underpins the system concept in innovation adoption and diffusion of agricultural technologies. It is well acknowledged that an extension training service or farmers' field school type of service may emerge as an important mechanism not only for disseminating information about new farming technology, but also crucial for the promotion of newly developed techniques to rural farmers, who otherwise lack the knowledge of and avenues to new technologies on their own as well as in increasing agricultural productivity and farm income (Azikiwe et al ., 2013). However, it is also found that all the farmers did not opt for the service or access the training or extension services.…”
Section: Methodsmentioning
confidence: 99%
“…A successful expansion program begins with the definition of specific objectives, which are the basis for defining work processes and evaluating implementation performance. Responding to the ever-changing demands of many rural communities around the world is an important issue for extension services, as extension workers must have the skills, knowledge and ability to help communities respond to these changes and challenges (Agholor et al, 2013). Mihaylov and Perkins (2014) emphasized that civic action is a joint effort of the government and non-profit organisations for the practical, cultural and democratic strengthening of the community.…”
Section: Related Literaturementioning
confidence: 99%